2008
DOI: 10.1363/4003408
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Programs to Increase Contraceptive Use Among Adult Women: A Review of Experimental and Quasi‐Experimental Studies

Abstract: Very few studies have evaluated interventions to increase contraceptive use among adult women. A research plan that rigorously assesses the impact of different approaches to increasing contraceptive use among adult women should be an integral part of any long-term effort to prevent unintended pregnancy in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Furthermore, few articles specifically address the relationship between counseling and contraceptive initiation or continued use 10 . Recent data from the National Survey of Family growth showed that women who received contraceptive counseling in the past year had an 80% decreased risk of contraception non-use 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, few articles specifically address the relationship between counseling and contraceptive initiation or continued use 10 . Recent data from the National Survey of Family growth showed that women who received contraceptive counseling in the past year had an 80% decreased risk of contraception non-use 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of what we can do in the clinical setting for women who are not very sure or have low intentions to use contraception is extremely limited. 28 Research is needed to determine how to accurately assess contraceptive intent in the clinical setting and how to effect it through counseling interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, efforts to reduce unintended pregnancy have primarily focused on improving education and knowledge about methods or on increasing access to contraceptive services and methods. 6,7 These efforts, however, have not to date made a substantial dent in the national rate of unintended pregnancy. Although hopes remain that widespread access to no-cost contraception under the Affordable Care Act may yet change the national landscape, there is a clear need to also consider the larger socio-cultural contexts in which pregnancy and contraceptive decision making occur.…”
Section: Introductionmentioning
confidence: 99%